1990
DOI: 10.1115/1.2909434
|View full text |Cite
|
Sign up to set email alerts
|

Complex Wavespeed and Hydraulic Transients in Viscoelastic Pipes

Abstract: The classic formula for waterhammer wavespeed is extended to calculate the complex-valued, frequency-dependent wavespeed in a viscoelastic pipe, which takes into account the effect of viscoelasticity of pipe wall material on wave propagation. With the complex wavespeed, the standard impedance or transfer matrix is directly used to analyze resonating conditions in systems including viscoelastic pipes, and the impulse response method presented previously by the authors is applied to compute nonperiodic transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 0 publications
0
22
0
2
Order By: Relevance
“…To model the pipe wall viscoelastic effects for transient pressure waves, instead of the use 221 of an additional term for the retarded strain, * a was used in the classic continuity equation 222 for elastic pipes to replace the elastic wave speed (Rieutord 1982;Suo and Wylie 1990 the mechanical characteristics of viscoelastic pipelines (an instantaneous elastic strain 236 followed by a retarded strain) lead to a frequency-dependent wave speed. As a result, the 237 pipeline viscoelasticity is more suitable to be analyzed in the frequency domain, where the 238 pipe response to loadings with various frequencies can be studied independently.…”
Section: Ve F E I T T Amentioning
confidence: 99%
“…To model the pipe wall viscoelastic effects for transient pressure waves, instead of the use 221 of an additional term for the retarded strain, * a was used in the classic continuity equation 222 for elastic pipes to replace the elastic wave speed (Rieutord 1982;Suo and Wylie 1990 the mechanical characteristics of viscoelastic pipelines (an instantaneous elastic strain 236 followed by a retarded strain) lead to a frequency-dependent wave speed. As a result, the 237 pipeline viscoelasticity is more suitable to be analyzed in the frequency domain, where the 238 pipe response to loadings with various frequencies can be studied independently.…”
Section: Ve F E I T T Amentioning
confidence: 99%
“…The viscoelasticity of the polycarbonate may affect the wave speed and damping (Meißner & Frank 1977;Gally, Güney & Rieutord 1979;Suo & Wylie 1990;Covas et al 2004). The unsteady wall friction may also have some impact on the wave damping (Bergant 2001).…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…Their analytic model compared well with the experimental results over a frequency range of 0-3 kHz. In addition to their developed model, the data was compared with the visco-elastic model developed by Suo and Wylie [84] in which the axial motion of the pipe was neglected; it was shown that Suo and Wylie's model approximated the experimental data below frequencies of 1 kHz.…”
Section: Rachid and Stuckenbruck [75] Combined A Kelvin-voigt Linear mentioning
confidence: 99%